What will be the value of the expression $\sin \left[ {2{{\cos }^{ - 1}}\cot \left( {2{{\tan }^{ - 1}}\dfrac{1}{2}} \right)} \right]$.
Answer
Verified
510.6k+ views
Hint: In this problem we have to find the value of the given expression, use the basic conversion techniques of various inverse trigonometric ratios into one another and simplify using the various inverse trigonometric identities, to reach the answer.
Complete step-by-step answer:
Given equation is
$\sin \left[ {2{{\cos }^{ - 1}}\cot \left( {2{{\tan }^{ - 1}}\dfrac{1}{2}} \right)} \right]$
As we know $2{\tan ^{ - 1}}A = {\tan ^{ - 1}}\dfrac{{2A}}{{1 - {A^2}}}$
So use this property in above equation we have,
$ \Rightarrow \sin \left[ {2{{\cos }^{ - 1}}\cot \left( {{{\tan }^{ - 1}}\dfrac{{2 \times \dfrac{1}{2}}}{{1 - {{\left( {\dfrac{1}{2}} \right)}^2}}}} \right)} \right]$
Now on simplifying we have,
$ \Rightarrow \sin \left[ {2{{\cos }^{ - 1}}\cot \left( {{{\tan }^{ - 1}}\dfrac{4}{3}} \right)} \right]$
Now as we know ${\tan ^{ - 1}}\theta = {\cot ^{ - 1}}\dfrac{1}{\theta }$ so, use this property in above equation we have,
$ \Rightarrow \sin \left[ {2{{\cos }^{ - 1}}\cot \left( {{{\cot }^{ - 1}}\dfrac{3}{4}} \right)} \right]$
Now cot and cot inverse is cancel out
$ \Rightarrow \sin \left[ {2{{\cos }^{ - 1}}\dfrac{3}{4}} \right]$
Now as we know ${\cos ^{ - 1}}A + {\cos ^{ - 1}}B = {\cos ^{ - 1}}\left( {AB - \sqrt {\left( {1 - {A^2}} \right)\left( {1 - {B^2}} \right)} } \right)$ so, use this property in above equation we have,
$ \Rightarrow \sin \left[ {{{\cos }^{ - 1}}\left( {\dfrac{3}{4}.\dfrac{3}{4} - \sqrt {\left( {1 - {{\left( {\dfrac{3}{4}} \right)}^2}} \right)\left( {1 - {{\left( {\dfrac{3}{4}} \right)}^2}} \right)} } \right)} \right]$
$ \Rightarrow \sin \left[ {{{\cos }^{ - 1}}\left( {\dfrac{9}{{16}} - \left( {1 - {{\left( {\dfrac{3}{4}} \right)}^2}} \right)} \right)} \right]$
$ \Rightarrow \sin \left[ {{{\cos }^{ - 1}}\left( {\dfrac{9}{{16}} - \left( {1 - \dfrac{9}{{16}}} \right)} \right)} \right] = \sin \left[ {{{\cos }^{ - 1}}\left( {\dfrac{9}{{16}} - \dfrac{7}{{16}}} \right)} \right]$
$ = \sin \left[ {{{\cos }^{ - 1}}\left( {\dfrac{2}{{16}}} \right)} \right] = \sin \left[ {{{\cos }^{ - 1}}\left( {\dfrac{1}{8}} \right)} \right]$……………….. (1)
Now let $y = {\cos ^{ - 1}}\left( {\dfrac{1}{8}} \right)$
$ \Rightarrow \cos y = \dfrac{1}{8}$
Now as we know that ${\sin ^2}y + {\cos ^2}y = 1$
$
\Rightarrow {\sin ^2}y + {\left( {\dfrac{1}{8}} \right)^2} = 1 \\
\Rightarrow {\sin ^2}y = 1 - \dfrac{1}{{64}} = \dfrac{{63}}{{64}} \\
\Rightarrow \sin y = \sqrt {\dfrac{{63}}{{64}}} = \sqrt {\dfrac{{7 \times 9}}{{8 \times 8}}} = \dfrac{3}{8}\sqrt 7 \\
$
$ \Rightarrow y = {\sin ^{ - 1}}\dfrac{{3\sqrt 7 }}{8}$
Now substitute this value in equation (1) we have
$ \Rightarrow \sin \left[ {{{\cos }^{ - 1}}\left( {\dfrac{1}{8}} \right)} \right] = \sin \left[ {{{\sin }^{ - 1}}\dfrac{{3\sqrt 7 }}{8}} \right]$
Now the sin and sin inverse is canceled out.
$ \Rightarrow \sin \left[ {2{{\cos }^{ - 1}}\cot \left( {2{{\tan }^{ - 1}}\dfrac{1}{2}} \right)} \right] = \dfrac{{3\sqrt 7 }}{8}$
Hence option (a) is correct.
Note: Whenever we face such type of problems the basics is knowing about the simple inverse trigonometric identities like $2{\tan ^{ - 1}}A = {\tan ^{ - 1}}\dfrac{{2A}}{{1 - {A^2}}}$ and many others are being mentioned above. Such problems are more formula based thus having a good grasp over the identities will help in getting on the right track to reach the answer.
Complete step-by-step answer:
Given equation is
$\sin \left[ {2{{\cos }^{ - 1}}\cot \left( {2{{\tan }^{ - 1}}\dfrac{1}{2}} \right)} \right]$
As we know $2{\tan ^{ - 1}}A = {\tan ^{ - 1}}\dfrac{{2A}}{{1 - {A^2}}}$
So use this property in above equation we have,
$ \Rightarrow \sin \left[ {2{{\cos }^{ - 1}}\cot \left( {{{\tan }^{ - 1}}\dfrac{{2 \times \dfrac{1}{2}}}{{1 - {{\left( {\dfrac{1}{2}} \right)}^2}}}} \right)} \right]$
Now on simplifying we have,
$ \Rightarrow \sin \left[ {2{{\cos }^{ - 1}}\cot \left( {{{\tan }^{ - 1}}\dfrac{4}{3}} \right)} \right]$
Now as we know ${\tan ^{ - 1}}\theta = {\cot ^{ - 1}}\dfrac{1}{\theta }$ so, use this property in above equation we have,
$ \Rightarrow \sin \left[ {2{{\cos }^{ - 1}}\cot \left( {{{\cot }^{ - 1}}\dfrac{3}{4}} \right)} \right]$
Now cot and cot inverse is cancel out
$ \Rightarrow \sin \left[ {2{{\cos }^{ - 1}}\dfrac{3}{4}} \right]$
Now as we know ${\cos ^{ - 1}}A + {\cos ^{ - 1}}B = {\cos ^{ - 1}}\left( {AB - \sqrt {\left( {1 - {A^2}} \right)\left( {1 - {B^2}} \right)} } \right)$ so, use this property in above equation we have,
$ \Rightarrow \sin \left[ {{{\cos }^{ - 1}}\left( {\dfrac{3}{4}.\dfrac{3}{4} - \sqrt {\left( {1 - {{\left( {\dfrac{3}{4}} \right)}^2}} \right)\left( {1 - {{\left( {\dfrac{3}{4}} \right)}^2}} \right)} } \right)} \right]$
$ \Rightarrow \sin \left[ {{{\cos }^{ - 1}}\left( {\dfrac{9}{{16}} - \left( {1 - {{\left( {\dfrac{3}{4}} \right)}^2}} \right)} \right)} \right]$
$ \Rightarrow \sin \left[ {{{\cos }^{ - 1}}\left( {\dfrac{9}{{16}} - \left( {1 - \dfrac{9}{{16}}} \right)} \right)} \right] = \sin \left[ {{{\cos }^{ - 1}}\left( {\dfrac{9}{{16}} - \dfrac{7}{{16}}} \right)} \right]$
$ = \sin \left[ {{{\cos }^{ - 1}}\left( {\dfrac{2}{{16}}} \right)} \right] = \sin \left[ {{{\cos }^{ - 1}}\left( {\dfrac{1}{8}} \right)} \right]$……………….. (1)
Now let $y = {\cos ^{ - 1}}\left( {\dfrac{1}{8}} \right)$
$ \Rightarrow \cos y = \dfrac{1}{8}$
Now as we know that ${\sin ^2}y + {\cos ^2}y = 1$
$
\Rightarrow {\sin ^2}y + {\left( {\dfrac{1}{8}} \right)^2} = 1 \\
\Rightarrow {\sin ^2}y = 1 - \dfrac{1}{{64}} = \dfrac{{63}}{{64}} \\
\Rightarrow \sin y = \sqrt {\dfrac{{63}}{{64}}} = \sqrt {\dfrac{{7 \times 9}}{{8 \times 8}}} = \dfrac{3}{8}\sqrt 7 \\
$
$ \Rightarrow y = {\sin ^{ - 1}}\dfrac{{3\sqrt 7 }}{8}$
Now substitute this value in equation (1) we have
$ \Rightarrow \sin \left[ {{{\cos }^{ - 1}}\left( {\dfrac{1}{8}} \right)} \right] = \sin \left[ {{{\sin }^{ - 1}}\dfrac{{3\sqrt 7 }}{8}} \right]$
Now the sin and sin inverse is canceled out.
$ \Rightarrow \sin \left[ {2{{\cos }^{ - 1}}\cot \left( {2{{\tan }^{ - 1}}\dfrac{1}{2}} \right)} \right] = \dfrac{{3\sqrt 7 }}{8}$
Hence option (a) is correct.
Note: Whenever we face such type of problems the basics is knowing about the simple inverse trigonometric identities like $2{\tan ^{ - 1}}A = {\tan ^{ - 1}}\dfrac{{2A}}{{1 - {A^2}}}$ and many others are being mentioned above. Such problems are more formula based thus having a good grasp over the identities will help in getting on the right track to reach the answer.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE